Suggested Model for accounting disclosure proactive and reflect on the decisions of investors: Applied research in a sample of industrial companies listed on the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Often requires the investor to know the result of the company's activity contribute to the investor or by wanting to invest in them because profit or loss of the company affect positively or negatively in the price of shares of the company and with the end of the fiscal year delayed companies often to issue its financial statements after it is approved and audited by an observer External Auditor, From here came the idea of ​​research that appears to stakeholders of financial statements proactive appear, including actual figures for earlier stages have been prepared lists about lists and planned by the administration reflect the results of its phase remainder of the year as if they are (half a year or season or month) to offer At the end of the fiscal year and seen it all investors and speculators shares in the stock market has blending researchers between financial accounting and management in the preparation of the model proposed for the disclosure of accounting proactive, as it has been integrating the actual information that disclosed by the company progress as well as budgets overall key to provide financial statements that initial activity the company.      It is known that reports of Managerial Accounting is to use the procedure, but only as good intention of the management of the company and in order to help stakeholders make decisions sound economic and to strengthen transparency and accountability and to provide information in a time when the need is urgent and necessary and the lack of financial reports at the end of the financial year and the impossibility of providing actual information ( 100%) are detected these reports within the proposed model, which is expected to operate a vacuum in a series of accounting disclosure of listed companies to contribute in the Iraqi Stock Exchange (ISE).